Absurdnost' brodjačih sjužetov - Javornik, Miha (Slavica Tergestina, 2012)
While presupposing that every culture evolves based on its own specific terms, this discussion poses the question of how one of Russia's main cultural and literary characteristics emerges within these two realms. Following research on historical poetics on permanent theme and motif-related (subject) schemes, which form the basis of oral or written artistic expression and pass from one country to another, the question that poses itself is how these consequent "travelling themes" pass from one (according to A. Flaker) style formation into another, from one phase of literary and cultural devel-opment into another. The analysis addresses the emergence of a specific motif scheme in the creative process of N.V.Gogol that has led to the absurd consciousness, which in turn became, regardless of art form transformations, a kind of a constructive principle of Soviet and Russian culture of the 20th century.
Keywords: 20. st.; 20th century; absurdity; absurdnost; literane študije; literary studies; potovalne teme; ruska književnost; ruska kultura; Russian culture; Russian literature; Soviet culture; sovjetska kultura; travelling themes